Treatment of posttraumatic syringomyelia: evidence from a systematic review - Kleindienst, Andrea; Laut, Francisco Marin; Roeckelein, Verena; Buchfelder, Michael; Dodoo-Schittko, Frank (Acta Neurochirurgica, 2020)
Background: Following spinal cord injury (SCI), the routine use of magnetic resonance imaging (MRI) resulted in an incremental diagnosis of posttraumatic syringomyelia (PTS). However, facing four decades of preferred surgical treatment of PTS, no clear consensus on the recommended treatment exists. We review the literature on PTS regarding therapeutic strategies, outcomes, and complications. Methods: We performed a systematic bibliographic search on (“spinal cord injuries” [Mesh] AND “syringomyelia” [Mesh]). English language literature published between 1980 and 2020 was gathered, and case reports and articles examining syrinx due to other causes were excluded. The type of study, interval injury to symptoms, severity and level of injury, therapeutic procedure, duration of follow-up, complications, and outcome were recorded. Results: Forty-three observational studies including 1803 individuals met the eligibility criteria. The time interval from SCI to the diagnosis of PTS varied between 42 and 264 months. Eighty-nine percent of patients were treated surgically (n = 1605) with a complication rate of 26%. Symptoms improved in 43% of patients postoperatively and in 2% treated conservatively. Stable disease was documented in 50% of patients postoperatively and in 88% treated conservatively. The percentage of deterioration was similar (surgery 16%, 0.8% dead; conservative 10%). Detailed analysis of surgical outcome with regard to symptoms revealed that pain, motor, and sensory function could be improved in 43 to 55% of patients while motor function deteriorated in around 25%. The preferred methods of surgery were arachnoid lysis (48%) and syrinx drainage (31%). Conclusion: Even diagnosing PTS early in its evolution with MRI, to date, no satisfactory standard treatment exists, and the present literature review shows similar outcomes, regardless of the treatment modality. Therefore, PTS remains a neurosurgical challenge. Additional research is required using appropriate study designs for improving treatment options.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Etiology; Hydromyelia; Spinal cord injury; Syringomyelia; Trauma; Treatment